2015
DOI: 10.1111/bju.13368
|View full text |Cite
|
Sign up to set email alerts
|

Surgimesh M‐SLING® transobturator and prepubic four‐arm urethral sling for post‐prostatectomy stress urinary incontinence: clinical prospective assessment at 24 months

Abstract: ObjectiveTo assess tolerance and mid-term clinical outcomes of treatment, with a new four-arm mesh sling, of postprostatectomy incontinence (PPI) in men. Material and MethodsThis was a French multicentre prospective study that included 93 patients who underwent radical prostatectomy at least 1 year before Surgimesh M-SLING â implantation for the treatment of PPI. Data were collected preoperatively, and patients were followed at 3, 12 and 24 months postoperatively. Objective outcome measures included number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The main difference, however, appears to be that the bulbospongiosus muscle is incised and the central tendon is dissected and partially released akin to the AdVance MS. In this study with 2‐year follow up 34% were cured (no pads and 24 h pad test <2 g), 27% improved (reduction in daily urine loss >50%), and 19% were considered failures . Subjective urinary symptom profile scores statistically improved at 12 and 24 months compared to baseline.…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…The main difference, however, appears to be that the bulbospongiosus muscle is incised and the central tendon is dissected and partially released akin to the AdVance MS. In this study with 2‐year follow up 34% were cured (no pads and 24 h pad test <2 g), 27% improved (reduction in daily urine loss >50%), and 19% were considered failures . Subjective urinary symptom profile scores statistically improved at 12 and 24 months compared to baseline.…”
Section: Methodsmentioning
confidence: 71%
“…In this study with 2-year follow up 34% were cured (no pads and 24 h pad test <2 g), 27% improved (reduction in daily urine loss >50%), and 19% were considered failures. 30 Subjective urinary symptom profile scores statistically improved at 12 and 24 months compared to baseline. Seventy-one percent of patients were satisfied or very satisfied with treatment.…”
Section: France)mentioning
confidence: 88%
See 2 more Smart Citations
“…The authors concluded that Virtue male sling implantation should not be recommended. At 24 months follow‐up, Le Portz et al, 15 using a daily pad weight <2 g as success criteria, showed that with the M‐SLING®, another type of four‐arm mesh sling, 34.4% of patients were cured, 27.1% had improvement, and 19.4% were considered as failures. In a recent systematic review and meta‐analysis on the male sling, Meisterhofer et al 16 showed that the objective cure rate varies between 8.3% and 87.3% with a pooled proportion estimate of 0.50 (95% CI: 0.45–0.56).…”
Section: Discussionmentioning
confidence: 99%